Electrospun PAN/PVP/ZnO Nanofiber Membrane as a Photocatalyst for Methylene Blue Degradation under UV Irradiation - Rut Rabekka Gultom; Istiara Rizqillah Hanifah; Rizky Aflaha; Hannah Faye M. Austria; T.M. Subrahmanya; Januar Widakdo; Aditya Rianjanu (Green and Sustainable Materials Society, 2026)
Textile dye pollution remains a critical environmental concern, necessitating the development of efficient and recoverable photocatalysts for wastewater remediation. In this study, polyacrylonitrile/polyvinylpyrrolidone/zinc oxide (PAN/PVP/ZnO) nanofiber membranes were fabricated via electrospinning with varying ZnO loadings (0, 0.5, 1, and 2 mmol) and evaluated for the photocatalytic degradation of methylene blue (MB) under ultraviolet (UV) irradiation. Scanning electron microscopy (SEM) revealed continuous, bead-free nanofibers with mean diameters of 355–552 nm, and energy dispersive X-ray spectroscopy (EDS) confirmed systematic Zn incorporation up to 34.52 wt%. A comparative study demonstrated that heat treatment at 450 °C was essential for converting the Zn(NO3)2 precursor into the photocatalytically active ZnO phase. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the retention of the polymer matrix integrity. Among the tested formulations, PAN/PVP/ZnO-1 (1 mmol) exhibited the highest photocatalytic performance, achieving approximately 95% MB degradation within 180 min, with a pseudo-first-order rate constant of k = 0.0251 min−1 (R2 = 0.9926), approximately 9 times faster than the neat PAN/PVP membrane. Higher ZnO loading (2 mmol) resulted in reduced photocatalytic performance. These findings indicate that 1 mmol ZnO is the optimal loading for PAN/PVP nanofiber photocatalysts, offering a promising recoverable membrane system for photocatalytic dye removal from wastewater.